Does agri-business/small and medium enterprise investment scheme (AGSMEIS) impact on youth entrepreneurship development in sub-Saharan Africa? Evidence from Nigeria - Elda N. Okolo-Obasi; Joseph I. Uduji (African Governance and Development Institute (AGDI), 2021)
Purpose - The purpose of this paper is to critically examine the agri-business/small and medium investment schemes (AGSMEIS) in Nigeria. Its special focus is to investigate the impact of the AGSMEIS on youth entrepreneurship development in Nigeria. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially crosssectional, describing and interpreting the current situation. A total of 1,200 respondents were sampled across the six geopolitical zones of Nigeria. Findings - The results from the use of a combined propensity score matching (PSM) and logit model indicate that AGSMEIS initiative generates significance gains in empowering youths in enterprise development, and if enhanced will help many young people become entrepreneurs. Practical implications - This suggests that AGSMEIS initiative can facilitate youth's access to credit and help them become owners of small and medium enterprises. Social implications - It implies that investing in young people for small and medium enterprises could bring Nigeria into the modern economy and lift sub-Saharan Africa out of poverty. Originality/value - This research adds to the literature on youth entrepreneurship development's debate in developing countries. It concludes that targeting the young people in AGSMEIS should form the foundation of public policy for entrepreneurship, poverty alleviation, and economic development.
Keywords: 330; Agri-business/small and medium investment schemes (AGSMEIS); youth entrepreneurship development; sub-Saharan Africa